Overview of Bacterial Profile of Bloodstream Infections in the Intensive Care Unit (ICU): Single Center Observational Study at Dr. M. Djamil General Hospital, Padang, Indonesia - Rara Puspita Impelleren; Yulia, Dwi; Yoshie Anto Chicamy (HM Publisher, 2024)
Background: Bloodstream infection (BSI) is a condition characterized by positive blood cultures in patients who have systemic infections. Bloodstream infections have developed into a threat to public health worldwide with high mortality rates in intensive care settings. This study aims to determine the bacterial profile of BSI in the intensive care unit (ICU) of Dr. M. Djamil General Hospital Padang. Methods: This study is a retrospective descriptive study with a cross-sectional design from secondary data at the Microbiology and Medical Records Installation Laboratory of Dr. M. Djamil General Hospital Padang. All blood samples from patients aged ≥18 years in the ICU who are suspected of being infected will be cultured and identified with VITEK 2 in 2022. Results: A total of 243 blood samples consisted of 126 men (52%) and 117 women (48%) with the largest age range being 41-60 years (48%). The diagnosis of BSI was found in 94% with the most common comorbidities being malignancy (42%) and stroke (15%). The most common bacterial bloodstream infections were found in the ICU of Dr. M. Djamil General Hospital Padang., namely Gram-positive bacteria (66%) and coccus (66%). The most common type of bacteria identified with the VITEK 2 automatic tool is Staphylococcus hominis. Multidrug-resistant organisms (MDRO) found in this study were 8% with the most common causes, namely extended spectrum B-lactamase (ESBL). Blood samples in this study found bacteria due to contamination by 38%. Conclusion: The BSI bacterial profile found was mostly in the ICU of Dr. M. Djamil General Hospital Padang is a Gram-positive bacterium, coccus-shaped, Staphylococcus hominis and ESBL. Blood cultures found bacteria contaminated by 38%.